Adverse Pregnancy Outcomes and International Immigration Status: A Systematic Review and Meta-analysis - Samira Behboudi-Gandevani; Razieh Bidhendi-Yarandi; Mohammad Hossein Panahi; Abbas Mardani; Piret Paal; Christina Prinds; Mojtaba Vaismoradi (Ubiquity Press, 2022)
Background: Disparities in health outcomes between immigrant and native-origin populations, particularly pregnant women, pose significant challenges to healthcare systems. The aim of this systematic-review and meta-analysis was to investigate the risk of adverse pregnancy outcomes among immigrant-women compared to native-origin women in the host country. Methods: PubMed (including MEDLINE), Scopus, and Web of Science were searched to retrieve studies published in English language up to September 2020. All observational studies examining the prevalence of at least one of the short-term single pregnancy outcomes for immigrants who crossed international borders compared to native-origin pregnant population were included. The meta-prop method was used for the pooled-estimation of adverse pregnancy-outcomes' prevalence. For pool-effect estimates, the association between the immigration-status and outcomes of interest, the random-effects model was applied using the model described by DerSimonian and Laird. I2 statistic was used to assess heterogeneity. The publication bias was assessed using the Harbord-test. Meta-regression was performed to explore the effect of geographical region as the heterogeneity source. Findings: This review involved 11 320 674 pregnant women with an immigration-background and 56 102 698 pregnant women as the native-origin population. The risk of emergency cesarean section (Pooled-OR = 1.1, 95%CI = 1.0-1.2), shoulder dystocia (Pooled-OR = 1.1, 95%CI = 1.0-1.3), gestational diabetes mellites (Pooled-OR = 1.4, 95%CI = 1.2-1.6), small for gestational age (Pooled-OR=1.3, 95%CI = 1.1-0.4), 5-min Apgar less than 7 (Pooled-OR = 1.2, 95%CI = 1.0-1.3) and oligohydramnios (Pooled-OR = 1.8, 95%CI = 1.0-3.3) in the immigrant women were significantly higher than those with the native origin background. The immigrant women had a lower risk of labor induction (Pooled-OR = 0.8, 95%CI = 0.7-0.8), pregnancy induced hypertension (Pooled-OR = 0.6, 95%CI = 0.5-0.7) preeclampsia (Pooled-OR = 0.7, 95%CI = 0.6-0.8), macrosomia (Pooled-OR = 0.8, 95%CI = 0.7-0.9) and large for gestational age (Pooled-OR = 0.8, 95%CI = 0.7-0.8). Also, the risk of total and primary cesarean section, instrumental-delivery, preterm-birth, and birth-trauma were similar in both groups. According to meta-regression analyses, the reported ORs were not influenced by the country of origin. Conclusion: The relationship between the immigration status and adverse perinatal outcomes indicated a heterogenous pattern, but the immigrant women were at an increased risk of some important adverse pregnancy outcomes. Population-based studies with a focus on the various aspects of this phenomena are required to explain the source of these heterogenicities.